Changes in muscle biochemical composition withsize in snow-trout, Schizothorax richardsonii(Gray) - Basade, Yasmeen; Kapila, Suman; Kapila, Rajeev (Indian Journal of Fisheries, 2011)
Changes in the proportion of muscle biochemical constituents viz., protein, lipid,ash, glycogen, moisture and energy contents were examined sex wise in youngimmature snow trout, Schizothorax richardsonii (100-200mm size) collected froma Himalayan river, Kosi in Uttaranchal. Protein, lipid, ash (p<0.05) and glycogenand energy contents (p<0.01) increased significantly and moisture percentagedecreased significantly (p<0.05) in either sexes with increase in size of fishesfrom 100 to 200mm in total length. Analysis of relationship between fish bodyweight (Wb) with percent protein, lipid, ash, glycogen, moisture and energycontents in both sexes revealed significant correlations, indicating that reliableestimates of muscle biochemical composition and energy contents can be madefrom Wb in young immature snow trout.